INTERAKTIV TA’LIM TEXNOLOGIYALARI (Conference Zone, 2022)
оne of the directions of development of information technologies in education is the use of interactive technologies. The introduction of modern interactive technologies in the field of education allows teachers to qualitatively change the content, methods and organizational forms of education. The purpose of these technologies in education is to increase the intellectual potential of the information society and the quality of education at all levels of the education system.